Los patrones de la criminalidad en el estado de Chihuahua. El caso del abigeato en las últimas décadas del siglo XIX - Lopes, Maria-Aparecida (El Colegio de México, A.C., 2001)
Cattle stealing was the most prosecuted crime in the state of Chihuahua during the last decades of the nineteenth century, although the high presence of this theft in criminal statistics was not due exclusively to the widespread existence of rustling gangs. There were so many laws dedicated to prosecuting and punishing rustlers, that crimes of other kinds were "resolved" according to  these laws. This work draws attention to the fact that the great amount of  crimes registered as "rustling" were actually conflicts related with the  growing triumph of private property over rights of "use and  passage" ("de uso y de paso") of small-and medium-scale cattle  raisers who, according to the authority, carried out illegal cattling transactions.